Deep-sea mysteries - Gish, Melissa (Gish, Melissa. Down in the ocean., 2019)
Highlights the unique physical traits and behaviors of creatures that live at the bottom of the world's oceans. Includes a glossary, color photographs, and first-person accounts from scientists.